Bluetooth messanger / Nur Amanina Shamsudin & Nurul Fadhilah Azadddin - Azaddin, Nurul Fadhilah; Shamsudin, Nur Amanina (2015)
Bluetooth is wireless technology for transferring data between two devices that are in close proximity with each other. The name of Bluetooth reflects the Scandinavian origins of the technology. It is named after a 10th century Danish Viking. There are many example of short distance wireless such as infrared and WLAN. Now days, y generation use their own internet or WIFI to send chat with others. This requires expensive costs compare with Bluetooth. Main objective from are to develop such an application which enables users to communicate with each other. That because Bluetooth messenger is made because it not require cost and easy to chat each other and use within specific range. Bluetooth messenger don't have to connect with any wires or cable. It just need to on Bluetooth and pair it. Although it only enables for specific range (100 meter) but it reduce the electromagnetic interference. When using WIFI, sometimes it lost connection and must to connect back with the connection. This project will increase number of users who are using the Bluetooth or who are going for wireless technology. It not old fashioned style for this days, if the uses of Bluetooth is improved.